RISK ANALYSIS OF COCONUT PRODUCT MARKETING - Fausayana, Ine; Abdullah, Weka Gusmiarty; Dawid, La Ode (International Journal of Research -GRANTHAALAYAH, 2018)
The aim of this study was to analysis the risks of coconut products marketing in Kendari City. The results of this study described risk identification in three stage of marketing of coconut product, namely (a) Five risks identified at the stage of storaging; broken coconut fruit, unsold product, fire market, theft of coconut fruits, and market regulation; (b) Three risks identified at the stage of processing; broken coconut, coconut shell waste, and damage to processing facilities; and (c) Four risks identified at the stage of selling; unsold product, non-strategic selling locations, substitute goods, and competitors. Overall, the risk on coconut products marketing was mapped at low risk. High risk was more prevalent in the stage of processing, which was caused by the risk of coconut shell waste. While medium risk was more prevalent in the stage of storaging.